(3GdGbJUGO GdSjGSj ddYhdeI hGdJcfhdhLjG fMh QDjI LOjOI (B/s - (3YjSi, eMeO YHO GdTajYs ((3HjQhJ(B: s (3GdTQcI GdYGdejI ddcJGH(B, s, 2004)
(3GdYhdeI hGdJcfhdhLjG(B:(3YQV YGe hOQGSI MGdI,GdYhdeI Hjf GdYQH hTQb BSjG,bVGjG NGUI Yf GdJcfhdhLjG aj EWGQ GdYhdeIs
(3HHdjhZQGajG(B:(3U(B.337-347s
Keywords: (3GdGbJUGO SjGSjs; (3GdYhdeIs; (3GdeYdheGJs